The efficacy of supplementation of Liquid Livgrow vet on liver tonic and Performance in broiler chickens (Journal of Hama University, 2019)
The study was conducted on 100 birds of one of the commercial crossed of broiler chicken to identifying the impact of plant- livgrow vet as liquid form on the activation of nliver and improving the growth in broiler chicken. The study confirmed that there was mark-able significant differences between control and trail groups, the last group was added the livgrow-vet liquid to water during the complete trail. From one day age to 45 days age with concentrations (5 ml chicks stage, 5 ml grower chicks and 10 ml finishers stage/100 birds a day). As far the Activity of liver enzyme (AST-ALP-LDH) in blood sera in ages (15, 30, and 45 days) from the age of bird. The p Activity was less than 0.05 in all the breeding stages. The research confirmed there were significant differences in weight gain of the trail birds in age 45 days comparison with control group birds (p value > 0.05).